2017
DOI: 10.1530/ec-17-0032
|View full text |Cite
|
Sign up to set email alerts
|

Rising maternal circulating GH during murine pregnancy suggests placental regulation

Abstract: Placenta-derived hormones including growth hormone (GH) in humans contribute to maternal adaptation to pregnancy, and intermittent maternal GH administration increases foetal growth in several species. Both patterns and abundance of circulating GH are important for its activity, but their changes during pregnancy have only been reported in humans and rats. The aim of the present study was to characterise circulating profiles and secretory characteristics of GH in non-pregnant female mice and throughout murine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 44 publications
3
35
0
Order By: Relevance
“…As with the PRLR, growth hormone receptor and growth hormone-induced pSTAT5 are observed in the PVN. 28 Growth hormone secretion is elevated during the second half of pregnancy in mice 25 and plays a key role in metabolic adaptations during pregnancy. 43 In early pregnancy, PVN pSTAT5 levels were low, and did not reflect changes in prolactin.…”
Section: Discussionmentioning
confidence: 99%
“…As with the PRLR, growth hormone receptor and growth hormone-induced pSTAT5 are observed in the PVN. 28 Growth hormone secretion is elevated during the second half of pregnancy in mice 25 and plays a key role in metabolic adaptations during pregnancy. 43 In early pregnancy, PVN pSTAT5 levels were low, and did not reflect changes in prolactin.…”
Section: Discussionmentioning
confidence: 99%
“…These adaptations are thought to be mediated by hormones secreted during pregnancy, principally prolactin and placental lactogens (59). High amounts of GH are also secreted during pregnancy in both humans and rodents (9). In a recent study, we showed that ablation of GHR in the entire brain or in LepR-expressing cells improved the systemic insulin sensitivity of pregnant mice (51).…”
Section: Gh Action In the Cns Regulates Metabolismmentioning
confidence: 99%
“…During fasting, neuropeptide Y (NPY)-expressing neurons become active (6), and NPY secretion is responsible for decreasing GH pulsatility via the activation of the Y1 receptor (5). In addition to fasting, other conditions that induce increased GH secretion include hypoglycemia (7), physical exercise (8) and pregnancy (9).…”
Section: Introductionmentioning
confidence: 99%
“…17 By contrast, pituitary mGH production continues during pregnancy in the mouse, and its basal secretion increases from mid-pregnancy onward because the mouse placenta does not produce an equivalent to human PGH. 17…”
Section: Dupli C Ati On and The E Volutionary Succe Ss Of Pl Acentamentioning
confidence: 99%